Employment Tribunal Fees and the Rule of Law: R (Unison) v Lord Chancellor in the Supreme Court. (6th February 2018) - Ford, Michael
Abstract: In R (UNISON) v Lord Chancellor (Equality and Human Rights Commission Intervening ) the Supreme Court held that fees for bringing claims in the employment tribunal were unlawful both under common law and as a matter of EU law. The judgment has very significant implications for any system in which the enforcement of employment or social rights is left to individual claimants, the paradigmatic model adopted in the UK. Recent government policy has ignored the public function of individual tribunal claims in delivering employment rights at the systemic level, exemplified by the theoretical assumptions and justifications which lay behind the introduction of fees. The Supreme Court's analysis of the rule of law and the common law right of access to justice is in sharp conflict with these policies. I discuss the difference between the common law principles and the parallel principles in EU law and under Article 6 of the ECHR. The article explores the consequences of the judgment for cases rejected, dismissed or not brought owing to fees, and its longer-term implications for impediments to access to courts and tribunals, all the more important with Brexit on the horizon. The judgment represents an important triumph of the rule of law over the increased marketisation of legal rights.